SOCIAL COHESION AMONG COMMUNITY-DWELLING OLDER ADULTS WHO ARE HOMEBOUND OR WHO RECEIVE MEALS ON WHEELS SERVICES - Walsh, S (Innov Aging, 2018)
Social cohesion is a characteristic of communities rooted in norms of trust and reciprocity. Sometimes described as what holds us together, social cohesion is linked to a variety of health outcomes for older adults, including self-rated health status and overall mortality. Data from the National Health and Aging Trends Study (NHATS) were used to test the hypothesis that perceived social cohesion would be lower for certain vulnerable sub-groups of older adults: (1) the homebound and semi-homebound, and (2) recipients of Meals on Wheels services. NHATS uses a nationally representative sample of Medicare beneficiaries ages 65 and older. The 7,070 included in this analysis represent 38,834,686 community-dwelling older adults across the US, of whom 6,982,672 were homebound or semi-homebound and 379,865 reported receiving Meals on Wheels services. Social cohesion was calculated as the average level of agreement with three NHATS items: people in this community… know each other, are willing to help each other, and can be trusted. Homebound and semi-homebound individuals reported low social cohesion significantly more often than community-dwelling older adults who were not homebound. However, the prevalence of low social cohesion was not significantly different for respondents who reported receiving help from Meals on Wheels relative to those who did not receive services. This result may be an artifact of underreporting of Meals on Wheels in the NHATS dataset or it may suggest that home-delivered meal programs like Meals on Wheels are protective against low social cohesion – further research is warranted to ascertain which.